Simultaneously enhanced strength-ductility synergy and corrosion resistance in submerged friction stir welded super duplex stainless steel joint via creating ultrafine microstructure - Cao, Fujun; Huang, Guoqiang; Hou, Wentao; Ni, Ruiyang; Sun, Tao; Hu, Jinpeng; Shen, Yifu; Gerlich, Adrian P. (Journal of materials processing technology, 2022)
In this paper, submerged friction stir welding (SFSW), capable of significantly weakening the welding thermal cycle compared to conventional FSW, was employed on SAF2507 super duplex stainless steel (SDSS). An ultrafine grained (UFG) dual-phase microstructure, characterized by more uniformly distributed and balanced alpha (α) and gamma (γ) phases with average grain sizes of 0.96 and 0.77 µm, respectively, was achieved in the stir zone (SZ). Such unique microstructure leads to a synergistic enhancement of tensile strength and ductility in the longitudinal SZ at room temperature, which increases from 840 MPa to 18% under AFSW condition to 915 MPa - 22%. As well, this UFG dual-phase microstructure plays a crucial role in determining the resultant higher corrosion resistance. Combining with the reduced width of entire joint, a transverse SFSW joint with a remarkable increased total elongation was successfully achieved. In addition, the relatively lower residual stress across the whole joint actually contributed to the increment of ductility in the SFSW joint, as compared to the traditional FSW joint. The aforementioned results demonstrate an effective strategy in achieving a completely balanced UFG microstructure across the whole SZ during SFSW and a concurrent improvement of strength, elongation and corrosion resistance. [Display omitted] •Submerged FSW is first employed to avoid the undesirable phase transformation in SDSS.•The thermal cycle of stir zone during submerged FSW of SDSS is revealed for the first time.•A superior FSW joint with excellent combination of high strength and ductility is achieved.•The residual stress and anti corrosion behavior of the submerged FSW joint is discussed in detail.